Kualitas Sensoris Telur Pindang batik yang Disamak dengan Teh Hitam: Sensory Qualities of Pindang batik Eggs Tanned with Black Tea - Mudawaroch, Roisu Eny; Wibawanti, Jeki Mediantari Wahyu; Arifin, Hanung Dhidhik (Jurnal Riset Agribisnis dan Peternakan, 2024)
The purpose of this study was to determine the effect of tea leaf levels as a tanner on pindang batik egg organoleptic tests. The results of this study are expected to be useful as information for producers about the level of tea leaves as a tanning agent for organoleptic tests of pindang batik eggs. There is an influence of tea leaf levels as a tanner on the organoleptic test of pindang batik eggs. The material in this study was chicken eggs, tea leaves, salt, water and garlic. The study used was an experiment with a complete randomized design. The results of the analysis of the various effects of tea leaf levels as a tanner for pindang batik eggs showed no real difference (P>0.05) against the organoleptic test of pindang batik egg taste. The results of variety analysis showed a significant difference (P<0.05) from the organoleptic test of egg white color. Pindang batik eggs with a level of 0.25 percent tea leaves are most preferred by panelists because of the dense brown color of egg whites. The results of the variety analysis did not show a noticeable difference (P>0.05) from the organoleptic test of pindang batik egg yolk color. The results of variety analysis did not show a noticeable difference (P>0.05) against the organoleptic test of pindang batik egg odor. The results of the analysis of pindang batik egg variety showed a real difference (P<0.05) from the organoleptic test of pindang batik egg texture, with a liking level of 0.25%. The results of the variety analysis showed a significant difference (P<0.05) from the reception organoleptic test with the highest favorability at the level of 0.25%. Conclusion of the study There was a significant influence on egg white color, texture and acceptance of tea leaf tanning ingredients, and did not have a noticeable effect on egg yolk color, smell and taste of pindang batik eggs. It is recommended that in making pindang batik eggs, you should use a concentration of 0.25 tea leaves because it provides results that consumers like.